From yerba mate to its processors: an analysis of its territorial dynamics in São Mateus do Sul, PR, Brazil (Terr@ Plural, 2022)
The exploitation of yerba mate goes beyond economic issues, due to its insertion in a dynamic multidimensional territorial context. Therefore, the initial analysis of its construction occurs from the relations of the object/subject of study in the territory. The plot inherent to the territory is marked by the diversity of subjects,elements, and dynamics that compose the territorialities, resulting in a complexity specific to each territorial clipping. This paper seeks to understand the territorial dynamics of the exploitation of yerba mate from the municipality of São Mateus do Sul, a territorial cutout located in the southeastern part of Paraná State, which, alongwith five other municipalities, has the recognition of the Geographical Indication (GI) of yerba mate. The data and information analyzed point to contradictions between the planted and harvested area and asymmetric relations between the groups involved in the process, in a complex and dynamic network.
Keywords: Territorialities; Multidimensionality; Networks